Repair of cervicothoracic skin defects with extra-long transverse cervical flaps by stepwise pressure packing in children: a technical innovation - Kong, Liangliang; Xiong, Jiageng; Ji, Yi; Cui, Jie; Chen, Jianbing; Shen, Weimin (Frontiers in Pediatrics, 2023)
Objective: To investigate the clinical effect of prolonging predilated transverse cervical flap with Stepwise pressure packing for neck and chest lesions in children.A retrospective review of children with large cervicothoracic lesions admitted to our department from January 2011 to June 2021 was conducted to compare the surgical method of pedicled flaps with transverse cervical flaps after prolonging pre-expansion with the method of stepwise pressure packing. Among 58 included children, 22 (14 males and 8 females) were allocated to the extended and expanded transverse cervical flap with stepwise compression dressing group, and 36 (19 males and 17 females) to the transverse cervical flap group. The causes of skin defects were: scars (37 cases) and giant nevus (21 cases). The course of the disease ranged from 0.5 to 8 years. The two groups were compared in terms of child satisfaction, the occurrence of infection, recurrence of the contracture, secondary operation, and repaired area.In 22 cases of extended transverse cervical flaps, 8 cases were embedded with two expanders, resulting in a total of 30 expanded flaps, which were successfully transferred to the neck and chest without necrosis at the distal end of compression, with good effect. Comparison of pedicled transverse cervical flaps with stepwise pressure packing and pedicled transverse cervical flaps alone revealed no significant difference in child satisfaction, the occurrence of infection, recurrence of the contracture, and secondary surgery (all P>0.05). Yet, there was a significant difference in the repair area between two groups (P<0.05).Prolongation of pedicled cervical flaps after pre-expansion with stepwise pressure packing resulted in an effective method for repairing the large skin defect of children's face and neck caused by various diseases. In terms of increasing neck repair area, the operation of cervical flaps was significantly superior to the simple cervical flaps, and there was no significant difference in scar pain between the two groups.